Transdiagnostic Investigation of Impulsivity in Alcohol Use Disorder and Binge Eating Disorder With Eye-Tracking Methodology—A Pilot Study - Schag, Kathrin; Rauch-Schmidt, Magdalena; Wernz, Friederike; Zipfel, Stephan; Batra, Anil; Giel, Katrin E. (Frontiers in Psychiatry, 2019)
Objective: Patients with Alcohol Use Disorder (AUD) and patients with Binge Eating Disorder (BED) are characterized by increased impulsivity, i.e. increased reward sensitivity and diminished response inhibition. In this pilot study, we compare both disorders directly concerning impulsivity using disorder-specific stimuli to gain insight into the relationship of both disorders and underlying mechanisms. Methods: We compared eye movements of 23 women with BED (age M = 40.9), 21 patients with AUD (13 females, 8 males, age M = 46.6), and respectively age- and sex-matched control groups (BED-CG, AUD-CG). We measured reward sensitivity with the free exploration paradigm and response inhibition with the modified antisaccade paradigm. We presented disorder-specific stimuli vs. neutral stimuli, i.e. food stimuli in the BED and BED-CG, and alcohol stimuli in the AUD and AUD-CG. Results: BED and BED-CG initially fixated more often on food stimuli vs. neutral stimuli, whereas AUD-CG initially fixated more often on neutral stimuli vs. alcohol stimuli. AUD showed less initial fixations and shorter dwell times on both stimulus categories in comparison with the other groups. When saccades towards stimuli should be inhibited, BED made more errors in first saccades for both stimulus categories in comparison with AUD-CG, and in second saccades particularly for food stimuli in comparison with all other groups, whereas AUD did not differ from the control groups. Conclusions: This pilot study indicates that food and alcohol stimuli are at the first sight differently processed. Moreover, patients with BED and with AUD seem to process disorder-specific stimuli differently. Whereas patients with AUD avoid stimuli generally, patients with BED predominantly show deficits in inhibitory control.